2012
DOI: 10.1038/ejcn.2012.94
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of complementary foods and its association with diarrhoeal morbidity and nutritional status of Bangladeshi children

Abstract: BACKGROUND/OBJECTIVES:To examine the bacteriological quality of complementary foods (CF) and to correlate the results with diarrhoeal morbidity and nutritional status of Bangladeshi children aged 6-24 months. SUBJECTS/METHODS: A total of 212 CF samples were tested, of which 72 were collected immediately before the first time of feeding (p1 h of food preparation) and 140 were collected at second/third time of feeding from 140 households located in urban and rural areas of Bangladesh. Anthropometry, food frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 15 publications
8
65
0
Order By: Relevance
“…40 Similar to other studies, 2,41 we also found that the risk of incidence and severity of diarrhoea were significantly less among older children groups in all models tested. Children aged 6-11 months are in a critical transitional period because of the introduction of complementary food that leads them to be exposed to the environment, as well as pathogenic microorganisms, 42 which increase the risk of diarrhoeal diseases among young age group. In the final model, girls had significantly less risk of diarrhoea than boys after adjusting for all other potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…40 Similar to other studies, 2,41 we also found that the risk of incidence and severity of diarrhoea were significantly less among older children groups in all models tested. Children aged 6-11 months are in a critical transitional period because of the introduction of complementary food that leads them to be exposed to the environment, as well as pathogenic microorganisms, 42 which increase the risk of diarrhoeal diseases among young age group. In the final model, girls had significantly less risk of diarrhoea than boys after adjusting for all other potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Nigeria reported that most diarrhoeal episodes occurred in children aged less than two, which corresponded with the weaning period (7). A similar study conducted in Bangladesh found that 40% of complementary food consumed by children was contaminated with Escherichia coli, and this was mainly attributable to poor food preparation techniques (5).…”
Section: Introductionmentioning
confidence: 93%
“…[12][13][14] In one study in Bangladesh, 40% of complementary foods were contaminated with a high concentration of pathogenic bacteria. 12 Unhygienic preparation of foods can cause contamination. Food contact with unwashed hands can be a source of diarrhea pathogens.…”
Section: Introductionmentioning
confidence: 99%